[47] Management and outcomes of mesh complications in female pelvic floor surgery: Results of the York Mesh Salvage Centre - Mustafa Hilmy (Taylor & Francis Group, 2018)
Objective: To review the management and outcome of complications (erosion, extrusion, pain and obstruction) following urinary incontinence (UI) surgery. Stress UI (SUI) has been treated with synthetic mesh and implants procedures for >20 years with good success rates. A recent review indicated safety and efficacy of mid-urethral slings (MUS) for women with SUI. With increasing public and legal interest in litigation cases related to mesh complications, there is a growing need for surgeons to share their experiences to establish best practice care. York is one of the nationally recognised salvage centres for management of women with mesh-related problems. Methods: Retrospective review of all women who presented with complications related to mid-urethral tapes and implants to our unit since 2012. Results: In all, 64 patients referred with complications related to SUI surgery were included; the majority had their initial UI procedure in other units. The International Continence Society (ICS)/International Urogynecological Association (IUGA) Standardised Graft Complication Classification was used for adverse effect assessment. Patients were discussed in the pelvic floor multi-disciplinary team and reported to the Medicines and Healthcare Products Regulatory Authority (HMRA). Urethral erosions (14), five macroplastique resected and 10 MUS were excised ± Martius vaginal flap. Bladder erosions (seven): four tension-free vaginal tapes (TVTs), two transobturator tapes (TOTs), and one single-incision mini-sling (SIMS), excised laparoscopy + cystoscopy and two required open excision, with one still awaiting treatment. Vaginal extrusions (26) 12 TVTs, eight TVT-obturator, one SIMS, and in the remaining the type of tape was not clear from the history, 19 had excision of tape ± Martius vaginal flap and five are still awaiting treatment. In all, 17 patients had voiding dysfunction or pain and needed urethrolysis or tape excision. Recurrent SUI after salvage surgery occurred in 23% of patients, with the majority treated successfully with autologous pubovaginal slings or Bulkamid. Conclusion: Our centre follows NHS England Mesh group, British Association of Urological Surgeons (BAUS) and British Society of Urogynaecology (BSUG) recommendations. Such complications can result in disabling and catastrophic consequences and should be managed in specialist centres. This had led to growing surgical interest in other treatment options for SUI.